2020
DOI: 10.1016/j.ijscr.2020.11.040
|View full text |Cite
|
Sign up to set email alerts
|

Hemorrhagic synovial cyst: An unexpected cause of acute cervical spinal cord compression. Case report

Abstract: Highlights Chronic inflammation of the synovial cyst induces neovascularization of its wall leading to a possible intra-cystic bleeding. The different signal modulations on MRI are due to the variable consistency and density of the cystic fluid. Synovial cyst hemorrhage produces a sudden increase in the size of the lesion with compression of the spinal cord and nerve roots. Surgery is the appropriate treatment in case of synovial cyst wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…It has been reported that approximately 10% of lesions in the lumbar spine are associated with hemorrhage, but hemorrhagic juxta-facet cysts in the cervical spine are rare, and only 7 cases including our case have been reported so far (Table 1). [6][7][8][9][10][11] The average age of the 7 patients was 71 years old (range, 58-86 years), and the most common location was at the C7-T1 level in 3 cases (43%). Neck or back pain was present in 5 of the 7 patients, and myelopathy progressed rapidly and required emergency decompression surgery in 6 cases.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that approximately 10% of lesions in the lumbar spine are associated with hemorrhage, but hemorrhagic juxta-facet cysts in the cervical spine are rare, and only 7 cases including our case have been reported so far (Table 1). [6][7][8][9][10][11] The average age of the 7 patients was 71 years old (range, 58-86 years), and the most common location was at the C7-T1 level in 3 cases (43%). Neck or back pain was present in 5 of the 7 patients, and myelopathy progressed rapidly and required emergency decompression surgery in 6 cases.…”
Section: Discussionmentioning
confidence: 99%
“…However, the cysts may undergo sudden changes, especially if they are exposed to stress. Synovial cysts have been known to spontaneously resolve, [1] increase in size, [5] hemorrhage, [10] calcify, [8] or become infected. [2] is can lead to variable clinical presentations, with some patients presenting with no significant physical examination findings while others can present with severe myelopathy or even Brown Sequard syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…Gait disturbance Gait disturbance, early myelopathy C5-7 Laminoplasty; C7 laminectomy C2-3 Laminectomy Lyons, 2011 [5] Literature Review Multiple Locations Cervical radiculopathy/myelopathy Various Machino, 2012 [6] (L) C4-5 Myelopathy C3-7 Laminoplasty DS Kim, 2014 [3] (L) C7-T1 Acute myelopathy C7-T1 Laminectomy SW Kim, 2014 [4] (L) C7-T1 Brown-Sequard Syndrome C5-6 Laminoplasty; C7 Laminoctomy Correador, 2015 [2] (L) C5-6 Myeloradiculopathy C4-6 Laminectomy/Fusion Mustroph, 2019 [7] Bilateral C7-T1 Myeloradiculopathy C7-T1 Laminoctomy (bilateral) Radouane, 2020 [10] (L) C7-T1 Neck pain and acute LLE weakness, secondary to hemorrhage (R) C7-T1 Hemi Laminectomy C2-7: Second, third, fourth, fifth, sixth, seventh cervical vertebral bone, T1: First thoracic vertebra, L: Left, R: Right, RVE: Right ventricular enlargement, Bil: Bilateral, LE: Lower extremity, LLE: Left lower extremity another presented with lower extremity weakness and numbness. is is most likely due to a multitude of factors, such as the difference in cyst size and placement, leading to compression of either spinal cord, nerve roots, or both.…”
Section: Lesion Location Presenting Symptoms Treatmentmentioning
confidence: 99%